Pre-basic seed potato (Solanum tuberosum L.) production using temporary immersion bioreactors - Tapia, M.de L. (2018)
Potato is an important food and cash crop in Perú. Its production is limited due to seed quality, and other biotic and abiotic factors. Here we explore a new alternative for potato pre-basic seed production named temporary immersion bioreactor (TIB). Potato microtubers production using TIB comprises two phases: multiplication and microtuberization. During the multiplication phase, we used 50 segments of four nodes from a semi-solid medium with an immersion and frequency time of five minutes and three hours, respectively. In addition, a photoperiod of 16 hours of light and eight hours of darkness during 28 days were employed. For the microtuberization phase and under darkness conditions during 60 days, we used 80 g/l of sucrose and 30 ml/explant as a volume for the medium. Then, it was possible to obtain five, six, and 2.5 microtubers per explant of potato varieties “Canchan INIA”, “Capiro”, and “Papa 3”, respectively.